Story of Man’s Creation for Shelley’s Frankenstein: - Maryam Navidi; Abdolhossein Joodaki; Talat Dehpahlavan (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
This study is an attempt to examine ecofeminism in the patriarchal society of Frankenstein of Shelley. At first glance, the novel is a manifestation of the patriarchal world of Shelley because the male characters are present, and almost all of the women in the novel either kill or die. But it can be perceived that Shelley’s female characters are present in their own ways because they are present in nature, as a matter of fact, the female character’s absence and passivity are the emblems of their overwhelming presence so much that even the monster also has some feminine features, and he is used to being passive, because when he appears, it is either dark or moonlight, both of them have feminine attributes. The narrations of novel events are almost described in the sea, which is also the female symbol. Hence, Shelley tries to increase the women’s presence in her own ways in her novel through natural features. The presentation of natural elements influences Monster so much that he also reveals the feminine, goddess features. It can be concluded that the research method of this study is to find Shelley’s ecofeminism attributes, the actual presence of women, and their virtual absence due to ecofeminism, because Shelley has used their own specific ways to show that women are very present in her patriarchal society so much that even all of the male characters have dual features and the feminine features are not absent but they are very present in nature and characters of the novel. Therefore, women’s absence is Shelley’s method to reveal their absolute presence.